Precision Medicine for CRC Patients in the Veteran Population: State-of-the-Art, Challenges and Research Directions - Mohapatra, Shyam S. (Dig Dis Sci, 2018)
Colorectal cancer (CRC) accounts for ~9% of all cancers in the Veteran population, a fact which has focused a great deal of the attention of the VA’s research and development efforts. A field-based meeting of CRC experts was convened to discuss both challenges and opportunities in precision medicine for CRC. This group, designated as the VA Colorectal Cancer Cell-genomics Consortium (VA4C), discussed advances in CRC biology, biomarkers, and imaging for early detection and prevention. There was also a discussion of precision treatment involving fluorescence-guided surgery, targeted chemotherapies and immunotherapies, and personalized cancer treatment approaches. The overarching goal was to identify modalities that might ultimately lead to personalized cancer diagnosis and treatment. This review summarizes the findings of this VA field-based meeting, in which much of the current knowledge on CRC prescreening and treatment was discussed. It was concluded that there is a need and an opportunity to identify new targets for both the prevention of CRC and the development of effective therapies for advanced disease. Also, developing methods integrating genomic testing with tumoroid-based clinical drug response might lead to more accurate diagnosis and prognostication and more effective personalized treatment of CRC.